Context, mechanisms and outcomes of dementia special care units: An initial programme theory based on realist methodology. - Rebecca Palm (Public Library of Science (PLoS), 2021)
Background Dementia special care units represent a widely implemented care model in nursing homes. Their benefits must be thoroughly evaluated given the risk of exclusion and stigma. The aim of this study is to present an initial programme theory that follows the principles of realist methodology. The theory development was guided by the question of the mechanisms at play in the context of dementia special care units to produce or influence outcomes of interest in people with dementia. Methods The initial programme theory is based on qualitative interviews with dementia special care stakeholders in Germany and a realist review of complex interventions in dementia special care units. The interviews were analysed using content analysis techniques. For the realist review, a systematic literature search was conducted in four scientific databases; studies were appraised for quality and relevance. All data were analysed independently by two researchers. A realist informed logic model was developed, and context-mechanism-outcome (CMO) configurations were described. Results We reviewed 16 empirical studies and interviewed 16 stakeholders. In the interviews, contextual factors at the system, organisation and individual levels that influence the provision of care in dementia special care units were discussed. The interviewees described the following four interventions typical of dementia special care units: adaptation to the environment, family and public involvement, provision of activities and behaviour management. With exception of family and public involvement, these interventions were the focus of the reviewed studies. The outcomes of interest of stakeholders include responsive behaviour and quality of life, which were also investigated in the empirical studies. By combining data from interviews and a realist review, we framed three CMO configurations relevant to environment, activity, and behaviour management. Discussion As important contextual factors of dementia special care units, we discuss the transparency of policies to regulate dementia care, segregation and admission policies, purposeful recruitment and education of staff and a good fit between residents and their environment.